Content Analysis of Makassar City Regional Regulations on Local Economic Resources Management - Achmad Amzal Maulana; Ampauleng; Salma Abdullah; Fatimah, Sitti (LPPM STIEM BONGAYA, 2025)
Local economic resource (SDEL) management is a crucial aspect of local governance, particularly in the era of decentralization. This study analyzes the effectiveness of Makassar City Regional Regulation (Perda) Number 5 of 2020 concerning SDEL Management through a qualitative content analysis approach, focusing on the principles of good governance. The results indicate that although this Perda provides a basic framework for SDEL management, there are several weaknesses in the implementation of the principles of transparency, accountability, and public participation. Key findings of this study include: Inter-institutional coordination is not clearly regulated, potentially leading to overlapping authority and inefficiency. Public participation remains symbolic and limited to the socialization stage, without inclusive mechanisms for marginalized groups. The policy evaluation system focuses more on administrative outputs than on tangible impacts, such as increased MSME income. The theoretical implications of this study enrich the governmental science literature by highlighting the gap between regulatory design and governance practices at the local level. Practically, these findings can serve as a reference for other local governments in developing more effective and sustainable SDEL management policies.